Impact of gendered ingroup/outgroup ostracism on women's academic performances. Issue 3 (4th May 2017) - Cursan, Anthony; Bernstein, Michael J.; Pascual, Alexandre; Félonneau, Marie-Line
ABSTRACT: This study investigated the impact of ostracism (vs. inclusion) for women in a same-sex vs. opposite-sex group on their cognitive performances. Female participants played Cyberball with other women or men and were either included or excluded. Participants then had to engage in the performance tasks. Results showed that women's performance was decreased by ostracism in a math task (but not a verbal task) yet only in the same-sex condition. Furthermore, this result was obtained only among participants who did the numeric task first. No effect was observed in the verbal task. Two replications of the initial study were conducted using the math task. The result of the first study has been replicated one time. A meta-analysis revealed a small effect of ostracism on performance in the ingroup condition, whereas the effect seems to be non-existent in the outgroup condition. Results are discussed and future perspectives are proposed.